Implementation Of Htb And Cacti Methods For Bandwidth Allocation And Network Monitoring At SMA N 2 Bengkulu City - Oki Zainal Abidin; Hari Aspriyono; Abdussalam Al Akbar (Jurnal Media Computer Science, 2026)
SMAN 2 Bengkulu City is one of the senior high schools that has utilized computer networks to support teaching and learning activities, particularly in its computer laboratory. However, problems arise due to the absence of a system that can fairly distribute bandwidth and monitor connected devices. This study aims to implement the Hierarchical Token Bucket (HTB) method for bandwidth allocation and employ Cacti as an open-source network monitoring tool. HTB enables proportional bandwidth distribution by determining network usage priorities, while Cacti monitors devices based on IP addresses and presents the network conditions (active/inactive) in graphical form. The results indicate that the application of HTB improves the fairness of bandwidth distribution, while Cacti provides real-time information about network conditions, thereby supporting administrators in effectively managing the school’s network.